Characterizing corporate social responsibility (CSR) practices in the Philippines - Anonuevo, Augustus T. (UP Los Baños Journal, 2013)
Corporate Social Responsibilty (CSR) promises a healthy mix between promoting corporate interests and contributing to the public good. The article cites the experiences of some selected companies, corporate foundations, corporate networks, and consortia in the country. Based on a review of literature and reports networks of foundation and result of key informant of reviews, the following emerged as features of CSR practice in the country: 1)a growing awareness of CSR among companies but only a fraction of atonal number of corporation engaged in CSR activities: 2)philanthrophy/charity giving remains the main form of corporate giving but there is a rise in CSR /corporate citizenship efforts; 3) huge amounts for various projects and beneficiaries have been generated; corporations, foundations and consortia have pooled funds together and leveraged them with donor agencies and other partners to underwrite major projects/strategic interventions; and 4) projects on education and community programs receive most of the CSR funds.